Titanium alloy additive manufacturing wear-resistant layer and preparation method thereof
By using composite powder to prepare a wear-resistant layer on the surface of a titanium alloy substrate under normal temperature and pressure, the problems of weak bonding and high preparation cost in the prior art have been solved, and the high wear resistance and low cost of titanium alloy preparation have been achieved.
Patent Information
- Application Number
- CN202411378036.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
AI Technical Summary
Existing titanium alloy surface modification technologies suffer from problems such as weak bonding, high preparation costs, and the need for vacuum or inert gas protection, which affect their wear resistance and applications.
A wear-resistant layer was prepared on the surface of a titanium alloy substrate using composite powder (TiC 10%-15%, Ni alloy 11%-32%, Sc2O3 1%-2%, ZrOCl2·8H2O 0.5%-1%, balance WC) in air at room temperature and pressure via a laser coaxial powder feeding method. Combined with chemical reactions, multiple hard phases were formed to improve the bonding strength and wear resistance.
High bonding strength between the titanium alloy matrix and the wear-resistant layer was achieved at room temperature and pressure, which simplified the preparation process, reduced costs, and significantly improved the wear resistance of the titanium alloy.
Smart Images

Figure CN119265561A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal surface additive manufacturing, and specifically relates to a titanium alloy additive manufacturing wear-resistant layer and a preparation method thereof. Background Art
[0002] Titanium alloys have many advantages such as high specific strength, strong corrosion resistance, high temperature resistance and good biocompatibility. They are widely used in aerospace, biomedicine, automobile manufacturing and other fields. However, titanium alloys have low hardness and poor friction and wear properties, which seriously restrict the further application of titanium alloys. Surface modification technology is an important means to improve the wear resistance of titanium alloys. Commonly used surface modification technologies include surface coating, surface texturing, composite treatment, etc. Surface coating is a coating or plating prepared on the surface of titanium alloy substrate by physical or chemical methods, such as thermal spraying, plasma spraying, electroplating, chemical plating, micro-arc oxidation, vapor deposition, magnetron sputtering, etc. The surface coating or plating prepared by these methods has weak bonding with the titanium alloy substrate and is easy to fall off from the substrate. Laser additive manufacturing technology is a flexible and efficient surface modification technology. By synchronously delivering the designed powder to the laser light source, high-precision forming of the component is achieved. This manufacturing technology has the characteristics of concentrated energy, small heat-affected zone, fast cooling speed, and flexible powder composition system, and has broad application prospects.
[0003] Since the titanium element in titanium alloy has high binding energy with oxygen, it is very sensitive to elements such as oxygen and hydrogen. In order to prevent titanium alloy from combining with oxygen in a high temperature environment and weakening its binding property, titanium alloy laser cladding is currently usually carried out in a vacuum or inert gas protection environment, which will inevitably increase the complexity of the equipment and undoubtedly increase the manufacturing cost. In addition, the design of the powder needs to comprehensively consider the wear resistance and compatibility with the titanium alloy matrix to avoid the situation where the prepared powder cannot be melted into the titanium alloy matrix due to the poor compatibility of the powder composition with the titanium alloy matrix, resulting in unmelted or stress-falling off.
[0004] Based on this, providing a composite powder and a matching additive manufacturing process that can not only improve the wear resistance of titanium alloys, but also form a high bonding force with the titanium alloy matrix, and can be additively manufactured under normal temperature and pressure air conditions, is of great significance to improving the wear resistance of titanium alloys, simplifying the preparation operation of the wear-resistant layer, and reducing the manufacturing cost. It is also a technical problem that needs to be solved urgently. Summary of the invention
[0005] One of the purposes of the present invention is to provide a titanium alloy additive manufacturing wear-resistant layer that can improve the wear resistance of a titanium alloy substrate, has a high bonding strength with the titanium alloy substrate, and can be additively manufactured under normal temperature and pressure air conditions.
[0006] The second object of the present invention is to provide a method for preparing a titanium alloy additively manufactured wear-resistant layer which can improve the wear resistance of the titanium alloy substrate, has a high bonding strength with the titanium alloy substrate, and can be additively manufactured under normal temperature and pressure air conditions.
[0007] The technical solution adopted by the present invention to achieve one of the purposes is: to provide a titanium alloy additive manufacturing wear-resistant layer, wherein the titanium alloy additive manufacturing wear-resistant layer is made of composite powder as raw material, and is deposited on the surface of the titanium alloy substrate under normal temperature and pressure air conditions by using a laser coaxial powder feeding additive manufacturing method; The raw materials of the composite powder include, by weight percentage: TiC 10%-15%, Ni alloy 11%-32%, Sc2O31%-2%, ZrOCl2·8H2O 0.5%-1%, and the balance is WC; The composition of the titanium alloy matrix, measured by weight percentage, includes: Al 6.0%-6.3%, V 4.2%-4.5%, Fe0.1%-0.2%, C 0.01%-0.1%, Y1.1-2.2%, and the balance is Ti.
[0008] The overall idea and inventive principle of the present invention are as follows: In order to improve the wear resistance of the titanium alloy matrix, in the preliminary research work of the present invention, the friction and wear failure behavior of the titanium alloy was first analyzed, and the composite powder was theoretically designed in combination with the characteristics of the laser light source and the characteristics of the additive manufacturing process. Subsequently, laser additive manufacturing experiments were carried out on new titanium alloy plates. The friction and wear properties of the prepared wear-resistant layer were discussed from various analysis angles. Finally, a composite powder formula suitable for laser additive manufacturing was obtained, which has the advantages of simple preparation method, economical and efficient, flexible and controllable wear-resistant layer.
[0009] In the selection and design of composite powder formula, it is necessary to comprehensively consider the role of different alloy elements in the rapid solidification of the laser additive manufacturing process and the melting and decomposition behavior of each powder component. At the same time, based on the basic knowledge of metallurgical physical chemistry and the kinetic behavior of the solidification process of multi-component alloys, it is expected to form a hard phase in the subsequent solidification process to effectively improve the wear resistance.
[0010] In the composite powder provided by the present invention, WC is the main alloy element, which can undergo a variety of metallurgical chemical reactions with Ti in the matrix under the action of a high-energy laser beam to form different intermediate phases or final phases, thereby improving wear resistance. WC can react with Ti to form a W2C intermediate phase and a hardened phase TiC according to chemical reaction formula (1), and the intermediate phase W2C can further react with Ti in the matrix to form W atoms and TiC, as shown in chemical formula (2). The decomposed W atoms can further combine with TiC to form (Ti, W) x C 1-x phase, as shown in chemical formula (3).
[0011] 2WC+Ti→W2C+TiC(1) W2C+Ti→2W+TiC(2) W+TiC→(Ti,W) x C 1-x (3) In the manufacturing process of the wear-resistant layer on the surface of titanium alloy, the bonding strength between the wear-resistant layer and the substrate needs to be considered. Nickel alloy is an important strengthening element of titanium alloy. Nickel has a face-centered cubic crystal structure. It can be dissolved into the interior of the titanium alloy during the laser melting process, thereby achieving a stable bond between the wear-resistant layer and the substrate. During the laser melting process, a γ-Ni phase can be formed to improve the bonding strength of the wear-resistant layer. When selecting the nickel content, when the nickel content is too low, the amount of nickel dissolved in titanium is small, and the cladding layer cannot be guaranteed to have a good bonding strength with the substrate; if the nickel content is high, its content in the form of solid solution is large, and more nickel atoms will reduce wear resistance and weaken the friction and wear performance of the wear-resistant layer. The present invention uses thermodynamic software to calculate and based on a large number of previous scientific experimental results, the mass percentage of Ni alloy powder is selected to be 11%-32%.
[0012] TiC is a common wear-resistant material with the advantages of high hardness, low price, wide adaptability, etc. In the present invention, TiC in the wear-resistant layer can be used as the original hardening phase to provide a basic strengthening effect. Studies have shown that if the TiC content is too little, the anti-friction and wear effect is weak; if the TiC content is too high, solidification internal stress is easily formed, and a large number of cracks appear on the surface of the wear-resistant layer. At the same time, considering that the matrix WC in the composite powder can be decomposed to form W and C atoms, C atoms can also further combine with Ti to form TiC (as shown in chemical formulas (4) and (5)). Therefore, the content of TiC needs to comprehensively consider the amount of other components WC, ZrOCl2·8H2O and Sc2O3 in the composite powder, and achieve better wear-resistant effect by adjusting the ratio of the four. This application determines that the mass percentage of TiC in the composite powder is 10%-15% through preliminary exploration and machine learning methods.
[0013] WC→W + C(4) Ti + C → TiC(5) Rare earth oxides are important additive elements for wear-resistant layers, which can change the structural morphology of the wear-resistant layer, refine the grains and purify the organizational structure. Sc2O3 is an important rare earth oxide. The appropriate addition can effectively inhibit the growth of columnar crystals, reduce the dilution rate of the substrate during laser additive manufacturing, and improve the material utilization efficiency. In addition, cracks and pores are important defects in laser additive manufacturing of wear-resistant layers. Sc2O3 can reduce the coating porosity and crack productivity during the melting process, thereby improving the forming quality of the wear-resistant layer.
[0014] ZrOCl2·8H2O is a unique wear-resistant enhancement component. It can preferentially decompose to form ZrO2 and Cl2 (as shown in Chemical Formula 6) under the excitation of laser high energy density. ZrO2 has good interfacial compatibility with titanium alloy, which can reduce the crack tendency and enhance the wear resistance of the additive manufacturing layer. Furthermore, during the laser additive manufacturing process, the Cl2 formed by the decomposition of ZrOCl2·8H2O can form a local protective atmosphere environment to prevent oxygen from oxidizing the titanium alloy.
[0015] ZrOCl2→ZrO2+Cl2(6) The titanium alloy matrix used in the present invention has a high aluminum content of 6.0%-6.3%, which can react with Ti to form products during the laser additive manufacturing process. The Y element in the titanium alloy can participate in the metallurgical reaction process to inhibit the formation of cracks during the laser additive manufacturing process. During the additive manufacturing process, the Al in the titanium alloy can react with the Ti in the molten pool to form a Ti3Al product (as shown in chemical formula 7), and the molten Ti can also react with the Ni in the powder to form a Ti2Ni phase (as shown in reaction formula 8). The formation of Ti3Al and Ti2Ni helps to improve the metallurgical bonding between the wear-resistant layer and the matrix while playing a lubricating role, thereby improving the bonding and wear resistance of the wear-resistant layer and the matrix.
[0016] 3Ti + Al → Ti3Al(7) 2Ti +Ni → Ti2Ni(8) Furthermore, based on a large number of previous research experiments, it was found that in the formula of the composite powder, when WC reacts physically and chemically with Ti in the matrix, and the formed TiC new phase satisfies a certain relationship with the original TiC strengthening phase in the powder, the wear resistance of the wear-resistant layer can be further improved. Preferably, in combination with previous theoretical research and experimental data, in the composition of the composite powder raw material, when the weight percentages of WC, TiC, Sc2O3 and ZrOCl2·8H2O meet the following formula (9), the improvement of wear resistance is most significant.
[0017] W WC = 1.8 W TiC +9 W Sc2O3 +2 W ZrOCl2·8H2O +26%(9) In formula (9), W WC is the weight percentage of WC in the composite powder, W TiC is the weight percentage of TiC in the composite powder, W Sc2O3is the weight percentage of Sc2O3 in the composite powder, W ZrOCl2·8H2O is the weight percentage of ZrOCl2·8H2O in the composite powder.
[0018] Furthermore, among the raw materials of the composite powder, the purity of WC, TiC, Sc2O3 and ZrOCl2·8H2O is above 99.99%.
[0019] Furthermore, in the raw materials of the composite powder, the composition of the Ni alloy includes, by weight percentage, C 1%-1.1%, Fe 3.9%-4.1%, Si 4.4%-4.5%, Cr 11%-13%, B 5%-6%, Bi 1.2-2.4%, and the balance Ni. This new Ni alloy has a high solid solubility with the titanium alloy, which is beneficial to improving the bonding strength between the wear-resistant layer and the substrate.
[0020] Furthermore, the raw materials of the composite powder are all in powder form, the particle size of TiC and WC powders is 50-60 μm, the particle size of Ni alloy powder is 60-70 μm, the particle size of Sc2O3 powder is 10-20 μm, and the particle size of ZrOCl2·8H2O powder is 200-300 μm.
[0021] The technical solution adopted by the present invention to achieve the second purpose is: to provide a method for preparing a wear-resistant layer of a titanium alloy additive manufacturing according to one of the purposes of the present invention, comprising the following steps: S1. Weigh the raw materials of the composite powder according to the proportion, ball-mill them until they are fully mixed, and dry them to obtain the composite powder; S2. Under normal temperature and pressure air conditions, the composite powder is uniformly deposited on the surface of the titanium alloy substrate by laser coaxial powder feeding to obtain a wear-resistant layer.
[0022] Furthermore, in step S1, the ball milling speed is 260-300 r / min, and the ball milling time is 120-180 min. The raw materials of the composite powder used in the present invention can be mixed in an air environment at normal temperature and pressure, and do not need to be mixed in a vacuum or inert gas protection environment, which further simplifies the preparation process and flow.
[0023] Furthermore, in step S1, the drying treatment is performed by drying at a temperature of 80-100° C. and a drying time of 60-90 min.
[0024] Furthermore, in step S2, the composite powder is uniformly sprayed on the surface of the titanium alloy substrate by using a laser coaxial powder feeding method, and the composite powder is melted by using a laser as a heat source, and a wear-resistant layer is obtained after cooling in air.
[0025] Furthermore, in the laser coaxial powder feeding, the laser adopts a circular spot with a diameter of 3-4 mm, a laser scanning speed of 9-11 mm / s, a laser power of 2500-2600 W, and an overlap rate of 40%-50%.
[0026] Furthermore, during the metallurgical chemical reaction between the laser and the composite powder, the Ti in the titanium alloy can preferentially react with WC to form the intermediate product W2C and the strengthening phase TiC, which prevents the reaction of Ti with oxygen; in addition, the decomposition temperature of ZrOCl2·8H2O is relatively low, and the decomposed Cl2 can form a protective layer on the surface of the titanium alloy, preventing the reaction of oxygen with the titanium alloy. Therefore, the laser additive manufacturing of the present invention is carried out in the air at normal temperature and pressure, without the need for vacuum or inert gas protection environment, which greatly facilitates the preparation operation process and simplifies the preparation process, and also significantly reduces the manufacturing cost.
[0027] Further, based on the above analysis, it can be known that in the composite powder of the present invention, WC can react with Ti in the titanium alloy and TiC atoms in the composite powder under the action of a high-energy beam laser to form a variety of products. If the coaxial powder feeding speed is too fast and the thickness of the laid powder is too large, it is impossible to ensure that the composite powder is fully in contact with the titanium alloy matrix to carry out metallurgical physical and chemical reactions, thereby failing to form a wear-resistant strengthening phase; if the coaxial powder feeding speed is too low, the content of the hard phase formed is low, and the improvement of wear resistance is limited. At the same time, the dissolution and re-precipitation of the original strengthening phase of TiC in the composite powder also require external energy. Therefore, combined with the material and laser properties such as the chemical reaction enthalpy of WC and the matrix, decomposition energy, TiC heat capacity, ZrOCl2·8H2O binding energy, laser reflectivity and absorptivity, in step S2, the powder feeding rate of the laser coaxial powder feeding is preferably 16-18 g / min.
[0028] Furthermore, in the laser coaxial powder feeding, the carrier gas flow rate is 1.4-1.5 L / min.
[0029] Furthermore, the wear-resistant layer prepared by the present invention does not need to undergo subsequent heat treatment operations, but can be directly cooled in the air and can be used after simple machining.
[0030] Furthermore, the wear-resistant layer has a cladding thickness of 1-2 mm on the surface of the titanium alloy substrate.
[0031] Furthermore, the wear-resistant layer is WC, Ti2Ni, Ti3Al, (Ti, W) x C 1-x and γ-Ni composite structure. Among them, WC is in block form, (Ti, W) x C 1-xIt is cellular, γ-Ni is granular, and Ti2Ni and Ti3Al are symbiotic strips. Compared with the typical shear wear characteristics of titanium alloys, the wear-resistant layer of this complex phase structure shows abrasive wear characteristics, which improves the wear resistance of the titanium alloy matrix by improving the wear mechanism.
[0032] Compared with the prior art, the present invention has the following beneficial effects: (1) In order to improve the surface wear resistance of titanium alloy, the present invention adopts laser additive manufacturing to prepare a wear-resistant layer on the surface of titanium alloy substrate. The present invention combines the theoretical analysis of chemical reactions and previous scientific experiments to design a new type of composite powder. High-energy laser beam can promote the reaction of WC and Ti atoms in the composite powder to form a variety of products and promote the formation of hard phase TiC; W formed by the decomposition of WC can react chemically with TiC to form (Ti, W) x C 1-x phase, further improving the wear resistance, the decomposed C can also combine with Ti to form TiC; the TiC in the mixed powder can also serve as a hard phase to improve the basic wear resistance; the new Ni alloy and titanium alloy in the composite powder have a high solid solubility, which can improve the bonding strength between the wear-resistant layer and the substrate.
[0033] (2) The present invention uses the composite powder obtained by the above design to obtain a wear-resistant layer on the surface of the titanium alloy through a laser additive manufacturing method. The composite powder is mainly composed of WC, and both the intermediate product and the final product can enhance the wear resistance without side effects. The preparation process of the wear-resistant layer does not require heating or preheating the substrate, which can simplify the manufacturing process and reduce energy consumption.
[0034] (3) In the metallurgical chemical reaction process of the laser and the composite powder of the present invention, Ti in the titanium alloy can preferentially react with WC to form the intermediate product W2C and the strengthening phase TiC, thereby preventing the reaction of Ti with oxygen; in addition, the decomposition temperature of ZrOCl2·8H2O is relatively low, and the decomposed Cl2 can form a protective layer on the surface of the titanium alloy, thereby preventing the reaction of oxygen with the titanium alloy. Therefore, the above-mentioned laser additive manufacturing of the wear-resistant layer does not need to be carried out in a vacuum environment or a protective atmosphere created by a large amount of inert gas, but can be carried out in air at normal temperature and pressure, which greatly facilitates the preparation operation process and simplifies the preparation process, and also significantly reduces the manufacturing cost.
[0035] (4) Compared with the current methods for improving the wear resistance of titanium alloys, which mostly use surface modification technologies such as micro-arc oxidation, physical vapor deposition, plasma spraying, high-speed air fuel injection, etc., the present invention simplifies the preparation operation of the wear-resistant layer, reduces the manufacturing cost, and is more conducive to promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1This is a microscopic surface morphology of the wear-resistant layer obtained in Example 1 of the present invention, wherein A is WC and B is (Ti, W). x C (1-x) , C is γ-Ni, D is Ti2Ni-Ti3Al; Figure 2 The figure is a comparison of the macroscopic wear scar morphology of the wear-resistant layer and the titanium alloy substrate prepared in Example 1; wherein (a) is the titanium alloy substrate with the wear-resistant layer, and (b) is the titanium alloy substrate; Figure 3 The diagram is a comparison of the microscopic wear morphology of the wear-resistant layer and the titanium alloy substrate prepared in Example 1; wherein (a) is the titanium alloy substrate with the wear-resistant layer, and (b) is the titanium alloy substrate. DETAILED DESCRIPTION
[0037] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0038] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0039] The present invention provides a titanium alloy additive manufacturing wear-resistant layer, and the preparation method thereof comprises the following steps: Step 1: Prepare the raw materials of composite powder according to the following weight percentages: TiC 10%-15%, Ni alloy (by weight percentage, including: C 1%-1.1%, Fe 3.9%-4.1%, Si 4.4%-4.5%, Cr 11%-13%, B 5%-6%, Bi 1.2-2.4%, and the balance Ni) 11%-32%, Sc2O3 1%-2%, ZrOCl2·8H2O 0.5%-1%, and the balance WC; the above raw materials are all in powder form, the particle size of TiC and WC powders is 50-60μm, the particle size of Ni alloy powder is 60-70 μm, the particle size of Sc2O3 powder is 10-20 μm, and the particle size of ZrOCl2·8H2O powder is 200-300 μm. The prepared raw materials are ball-milled until fully mixed, and dried to obtain composite powder; Step 2: Under normal temperature and pressure air conditions, the composite powder obtained in step 1 is uniformly deposited on the surface of a titanium alloy substrate (by weight percentage, including: Al 6.0%-6.3%, V 4.2%-4.5%, Fe 0.1%-0.2%, C 0.01%-0.1%, Y1.1-2.2%, and the balance is Ti) by laser coaxial powder feeding to obtain a wear-resistant layer; in the laser coaxial powder feeding, the laser uses a circular spot with a diameter of 3-4mm, the laser scanning speed is 9-11mm / s, the laser power is 2500-2600 W, the overlap rate is 40%-50%, the powder feeding rate is 16-18 g / min, and the carrier gas flow rate is 1.4-1.5 L / min; the obtained wear-resistant layer does not need to undergo subsequent heat treatment operations and can be directly cooled in the air.
[0040] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited thereto.
[0041] The raw material composition of the composite powder, the titanium alloy matrix composition and the Ni alloy composition in Examples 1-4 of the present invention are shown in Tables 1-3 respectively (all in weight percentage wt.%).
[0042] Table 1
[0043] Table 2
[0044] Table 3
[0045] In Examples 1-4 of the present invention, during the laser coaxial powder feeding process, the main parameters are shown in Table 4 below.
[0046] Table 4
[0047] Example 1 This embodiment provides a titanium alloy additive manufacturing wear-resistant layer, and the preparation method thereof comprises the following steps: Step 1: Weigh the raw materials of the composite powder according to the mass percentage of each component, TiC 12%, Ni alloy 22.9%, Sc2O3 1.6%, ZrOCl2·8H2O 0.5%, and the balance WC, the particle diameters of TiC and WC powders are 55 μm, the particle diameters of Ni alloy powders are 60 μm, the particle diameters of Sc2O3 powders are 15 μm, and the diameter of ZrOCl2·8H2O is 200 μm; wherein, the Ni alloy comprises, by weight percentage, C 1%, Fe 4.0%, Si 4.4%, Cr 12%, B 5%, Bi 1.9%, and the balance Ni; and then mix them on a planetary ball mill to prepare the composite powder, and the mixing process is carried out in air at normal temperature and pressure.
[0048] Step 2: Use laser additive manufacturing technology to evenly sprinkle the composite powder prepared in step 1 on the surface of the titanium alloy (the composition of the titanium alloy matrix is calculated by weight percentage, Al 6.0%, V 4.3%, Fe 0.15%, C 0.04%, Y1.7%, and the balance Ti). The experimental environment is an air environment at normal temperature and pressure. The light source is a circular spot with a diameter of 3 mm, the laser scanning speed is 9 mm / s, the laser power is 2500W, the overlap rate is 40%, the powder feeding rate is 16 g / min, and the carrier gas flow rate is 1.4 L / min. Prepare the wear-resistant layer. After cooling in the air, the wear-resistant layer is obtained and can be used after simple machining.
[0049] The microstructure of the laser additive manufacturing wear-resistant layer prepared in this embodiment is as follows: Figure 1 As shown, through Figure 1 From the morphology observation and energy spectrum analysis in Table 5, it can be seen that the microstructure of the wear-resistant layer manufactured by additive manufacturing on the surface of titanium alloy is composed of WC, Ti2Ni, Ti3Al, (Ti, W) x C 1-x and γ-Ni composite structure. Among them, WC is in block form, (Ti, W) x C 1-x It is cellular, γ-Ni is granular, and Ti2Ni and Ti3Al are symbiotic strips. This type of complex phase structure can significantly improve the wear resistance of the titanium alloy matrix.
[0050] Table 5 Microstructure energy spectrum analysis results
[0051] Example 2 This embodiment provides a titanium alloy additive manufacturing wear-resistant layer, and the preparation method thereof comprises the following steps: Step 1: Weigh the raw materials of the composite powder according to the mass percentage of each component, TiC 11%, Ni alloy 26.4%, Sc2O3 1.5%, ZrOCl2·8H2O 0.6%, and the balance WC, the particle diameters of TiC and WC powders are 50 μm, the particle diameters of Ni alloy powders are 60 μm, the particle diameters of Sc2O3 powders are 20 μm, and the diameter of ZrOCl2·8H2O is 250 μm; wherein, the Ni alloy comprises, by weight percentage, C 1%, Fe 4.1%, Si 4.5%, Cr 12%, B 5%, Bi 2.1%, and the balance Ni, and then mix them on a planetary ball mill to prepare a composite powder, and the mixing process is carried out in air at normal temperature and pressure.
[0052] Step 2: Use laser additive manufacturing technology to evenly sprinkle the composite powder prepared in step 1 on the surface of the titanium alloy (the composition of the titanium alloy matrix is calculated by weight percentage, Al 6.2%, V 4.3%, Fe 0.18%, C 0.05%, Y1.9%, and the balance Ti). The experimental environment is an air environment at normal temperature and pressure. The light source is a circular spot with a diameter of 4 mm, the laser scanning speed is 10 mm / s, the laser power is 2600W, the overlap rate is 50%, the powder feeding rate is 17 g / min, and the carrier gas flow rate is 1.4 L / min. Prepare the wear-resistant layer. After cooling in the air, the wear-resistant layer is obtained and can be used after simple machining.
[0053] Example 3 This embodiment provides a titanium alloy additive manufacturing wear-resistant layer, and the preparation method thereof comprises the following steps: Step 1: Weigh the raw materials of the composite powder according to the mass percentage of each component, TiC 13.5%, Ni alloy 19.8%, Sc2O3 1.4%, ZrOCl2·8H2O 0.8%, and the balance WC, the particle diameters of TiC and WC powders are 60 μm, the particle diameters of Ni alloy powders are 65 μm, the particle diameters of Sc2O3 powders are 15 μm, and the diameter of ZrOCl2·8H2O is 300 μm; wherein, the Ni alloy comprises, by weight percentage, C 1.1%, Fe 4.1%, Si 4.5%, Cr 11%, B 6%, Bi 2.1%, and the balance Ni; and then mix them on a planetary ball mill to prepare the composite powder, and the mixing process is carried out in air at normal temperature and pressure.
[0054] Step 2: Use laser additive manufacturing technology to evenly sprinkle the composite powder prepared in step 1 on the surface of the titanium alloy (the composition of the titanium alloy matrix is calculated by weight percentage, Al 6.2%, V 4.4%, Fe 0.18%, C 0.06%, Y1.2%, and the balance Ti). The experimental environment is an air environment at normal temperature and pressure. The light source is a circular spot with a diameter of 3 mm, the laser scanning speed is 10 mm / s, the laser power is 2500W, the overlap rate is 40%, the powder feeding rate is 18 g / min, and the carrier gas flow rate is 1.5 L / min. Prepare the wear-resistant layer. After cooling in the air, the wear-resistant layer is obtained and can be used after simple machining.
[0055] Example 4 This embodiment provides a titanium alloy additive manufacturing wear-resistant layer, and the preparation method thereof comprises the following steps: Step 1: Weigh the raw materials of the composite powder according to the mass percentage of each component, TiC 14%, Ni alloy 18.7%, Sc2O3 1.4%, ZrOCl2·8H2O 0.7%, and the balance WC, the particle diameters of TiC and WC powders are 50 μm, the particle diameters of Ni alloy powders are 65 μm, the particle diameters of Sc2O3 powders are 20 μm, and the diameter of ZrOCl2·8H2O is 200 μm; wherein, the Ni alloy comprises, by weight percentage, C 1%, Fe 4.1%, Si 4.5%, Cr 13%, B 6%, Bi 2.3%, and the balance Ni; and then mix them on a planetary ball mill to prepare the composite powder, and the mixing process is carried out in air at normal temperature and pressure.
[0056] Step 2: Use laser additive manufacturing technology to evenly sprinkle the composite powder prepared in step 1 on the surface of the titanium alloy (the composition of the titanium alloy matrix is calculated by weight percentage, Al 6.2%, V 4.4%, Fe 0.15%, C 0.08%, Y2.1%, and the balance Ti). The experimental environment is an air environment at normal temperature and pressure. The light source is a circular spot with a diameter of 3 mm, the laser scanning speed is 11 mm / s, the laser power is 2500W, the overlap rate is 50%, the powder feeding rate is 17 g / min, and the carrier gas flow rate is 1.5 L / min. Prepare the wear-resistant layer. After cooling in the air, the wear-resistant layer is obtained and can be used after simple machining.
[0057] Example 5 The difference between this embodiment and embodiment 1 is that the weight percentages of the raw materials in the composite powder are adjusted to be: TiC 12%, Ni alloy 19%, Sc2O3 1.6%, ZrOCl2·8H2O 0.6%, and the balance WC. The other conditions and operating steps remain unchanged, and a wear-resistant layer is prepared on the surface of the titanium alloy substrate.
[0058] Example 6 The difference between this embodiment and embodiment 1 is that the parameters of laser additive manufacturing in step 2 are adjusted, specifically: the light source is a circular spot with a diameter of 3 mm, the laser scanning speed is 8 mm / s, the laser power is 2900W, the overlap rate is 40%, the powder feeding rate is 20 g / min, and the carrier gas flow rate is 1.4 L / min. The other conditions and operating steps remain unchanged, and a wear-resistant layer is prepared on the surface of the titanium alloy substrate.
[0059] Comparative Example 1 The difference between this comparative example and Example 1 is that the content of TiC in the composite powder is reduced, and the raw material composition of the composite powder is adjusted to: TiC 9.2%, Ni alloy 30.7%, Sc2O31.6%, ZrOCl2·8H2O 0.5%, and the balance is WC. The other conditions and operating steps remain unchanged, and a wear-resistant layer is prepared on the surface of the titanium alloy substrate.
[0060] Comparative Example 2 The difference between this comparative example and Example 1 is that the content of TiC in the composite powder is increased, and the raw material composition of the composite powder is adjusted to: TiC 16%, Ni alloy 11.7%, Sc2O3 1.6%, ZrOCl2·8H2O 0.5%, and the balance WC. The other conditions and operating steps remain unchanged, and a wear-resistant layer is prepared on the surface of the titanium alloy substrate.
[0061] Comparative Example 3 The difference between this comparative example and Example 1 is that the content of Sc2O3 in the composite powder is reduced, and the raw material composition of the composite powder is adjusted to: TiC 12%, Ni alloy 30.9%, Sc2O3 0.8%, ZrOCl2·8H2O 0.5%, and the balance WC. The other conditions and operating steps remain unchanged, and a wear-resistant layer is prepared on the surface of the titanium alloy substrate.
[0062] Comparative Example 4 The difference between this comparative example and Example 1 is that the content of Sc2O3 in the composite powder is increased, and the raw material composition of the composite powder is adjusted to: TiC 12%, Ni alloy 16.9%, Sc2O3 2.2%, ZrOCl2·8H2O 0.5%, and the balance is WC. The other conditions and operating steps remain unchanged, and a wear-resistant layer is prepared on the surface of the titanium alloy substrate.
[0063] Comparative Example 5 The difference between this comparative example and Example 1 is that the content of ZrOCl2·8H2O in the composite powder is reduced, and the raw material composition of the composite powder is adjusted to: TiC 12%, Ni alloy 24.1%, Sc2O31.6%, ZrOCl2·8H2O 0.1%, and the balance is WC. The other conditions and operating steps remain unchanged, and a wear-resistant layer is prepared on the surface of the titanium alloy substrate.
[0064] Comparative Example 6 The difference between this comparative example and Example 1 is that the content of ZrOCl2·8H2O in the composite powder is increased, and the raw material composition of the composite powder is adjusted to: TiC 12%, Ni alloy 20.5%, Sc2O31.6%, ZrOCl2·8H2O 1.3%, and the balance is WC. The other conditions and operating steps remain unchanged, and a wear-resistant layer is prepared on the surface of the titanium alloy substrate.
[0065] Comparative Example 7 The difference between this comparative example and Example 1 is that the Ni alloy in the composite powder is replaced with high-purity nickel, and the composition of the composite powder includes, by weight percentage: Ni 22.9%, Sc2O3 1.6%, ZrOCl2·8H2O 0.5%, and the balance WC. The other conditions and operating steps remain unchanged, and a wear-resistant layer is prepared on the surface of the titanium alloy substrate.
[0066] Comparative Example 8 The difference between this comparative example and Example 1 is that the type of titanium alloy substrate in step 2 of Example 1 is replaced, and the composition of the adjusted titanium alloy includes, by weight percentage, 0.5% Fe, 0.04% C, and the balance Ti. The other conditions and operating steps remain unchanged, and a wear-resistant layer is prepared on the surface of the pure titanium substrate.
[0067] Performance Testing The wear-resistant layers prepared in the embodiments of the present invention and the comparative examples were subjected to friction and wear performance tests. A friction and wear testing machine was used to simulate the service friction and wear environment. The wear rate of the prepared wear-resistant layers was measured according to the profile method and compared with the wear rate of the titanium alloy substrate under the same test conditions. The test results are shown in Table 6 below: Table 6
[0068] As can be seen from the above table, The wear rate of the wear-resistant layer obtained in Examples 1-4 of the present invention is 4.8×10 -8 -6.5×10 -8 mm 3 ·N -1 mm -1 , while the wear rate of the titanium alloy substrate under the same test conditions is 2.0×10 -7 -2.2×10 -7 mm 3 ·N -1 mm -1 It can be seen that the surface wear-resistant layer prepared by the present invention can greatly improve the wear resistance of titanium alloy. Figure 2 The comparison of the wear scar morphology of the laser cladding wear-resistant layer and the titanium alloy substrate prepared in Example 1 is shown in FIG. Figure 2 It can be seen that the wear-resistant layer prepared in Example 1 exhibits abrasive wear characteristics, while the titanium alloy substrate exhibits typical shear wear, which fully demonstrates that the wear-resistant layer with a special multiphase structure prepared in the present invention changes the wear mechanism of the titanium alloy.
[0069] The raw materials of the composite powder provided in Example 5 are all within the protection scope provided by the present invention, but the content of the raw materials does not satisfy formula (9) W WC = 1.8 W TiC +9 W Sc2O3 +2 W ZrOCl2·8H2O +26%, although the performance of the wear-resistant layer is improved compared with the titanium alloy substrate, the effect is not as significant as that of Examples 1-4. This shows that only when the components of the various raw materials of the composite powder satisfy the ratio relationship of the formula can a better wear-resistant effect be obtained. Randomly setting the component formula cannot obtain excellent wear resistance even within the range.
[0070] Example 6 uses different preparation process parameters from Examples 1-4, and adjusts the laser additive manufacturing parameters during the preparation process. The parameters exceed the range requirements. Although the performance of the wear-resistant layer is improved to a certain extent compared with the titanium alloy substrate, the effect is not as significant as that of Examples 1-4. This shows that laser additive manufacturing parameters play an important role in wear resistance. Only manufacturing parameters that match the composite powder in this application can obtain an ideal wear resistance effect. Simply adjusting the process parameters cannot obtain a good wear-resistant layer.
[0071] Compared with Example 1, Comparative Examples 1-6 respectively adjusted the amount of each raw material in the composite powder, and the prepared wear-resistant layers could not significantly improve the wear resistance of the titanium alloy substrate, which shows that in order to effectively improve the wear resistance, it is necessary to control the amount of each raw material of the composite powder within a reasonable range. In addition, Comparative Example 7 replaces the Ni alloy with high-purity nickel and Comparative Example 8 replaces it with pure titanium, and the wear resistance is not significantly improved, which shows that the selection of composite powder raw materials and the laser additive manufacturing method provided by the present invention have a better wear resistance improvement effect on titanium alloys of a specific composition.
[0072] In summary, in the present invention, the composite powder designed in this application is used, and the laser additive parameters and titanium alloy matching the powder are used to significantly improve the wear resistance of the titanium alloy. Simply trying to change the composite powder composition and manufacturing process parameters based on the knowledge known in the art or other public reports, or transferring the alloy powder ratio and manufacturing process parameters in this application to other alloys, cannot guarantee the desired effect.
[0073] The above are only preferred embodiments of the present invention, and are not intended to limit the implementation methods and protection scope of the present invention. Those skilled in the art should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the contents of the specification of the present invention should be included in the protection scope of the present invention.
Claims
1. A titanium alloy additive manufacturing wear-resistant layer, characterized in that: The titanium alloy additive manufacturing wear-resistant layer is made of composite powder as raw material, and is deposited on the surface of the titanium alloy substrate under normal temperature and pressure air conditions by using a laser coaxial powder feeding additive manufacturing method; The raw materials of the composite powder include, by weight percentage: TiC 10%-15%, Ni alloy 11%-32%, Sc2O3 1%-2%, ZrOCl2·8H2O 0.5%-1%, and the balance WC; The composition of the titanium alloy matrix includes, by weight percentage, 6.0%-6.3% Al, 4.2%-4.5% V, 0.1%-0.2% Fe, 0.01%-0.1% C, 1.1-2.2% Y, and the balance is Ti.
2. The titanium alloy additive manufacturing wear-resistant layer according to claim 1, characterized in that: Among the raw materials of the composite powder, the purity of WC, TiC, Sc2O3 and ZrOCl2·8H2O is not less than 99.99%.
3. The titanium alloy additive manufacturing wear-resistant layer according to claim 1, characterized in that: The composition of the Ni alloy in the raw materials of the composite powder includes, by weight percentage, C 1%-1.1%, Fe 3.9%-4.1%, Si 4.4%-4.5%, Cr11%-13%, B 5%-6%, Bi 1.2-2.4%, and the balance Ni.
4. The titanium alloy additive manufacturing wear-resistant layer according to claim 1, characterized in that: The raw materials of the composite powder are all in powder form, the particle size of TiC and WC powders is 50-60 μm, the particle size of Ni alloy powder is 60-70 μm, the particle size of Sc2O3 powder is 10-20 μm, and the particle size of ZrOCl2·8H2O powder is 200-300 μm.
5. The method for preparing a wear-resistant layer made of titanium alloy by additive manufacturing according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Weigh the raw materials of the composite powder according to the proportion, ball-mill them until they are fully mixed, and dry them to obtain the composite powder; S2. Under normal temperature and pressure air conditions, the composite powder is uniformly deposited on the surface of the titanium alloy substrate by laser coaxial powder feeding to obtain a wear-resistant layer.
6. The preparation method according to claim 5, characterized in that: In step S1, the ball milling treatment is carried out in air at normal temperature and pressure, the rotation speed of the ball milling treatment is 260-300 r / min, and the ball milling treatment time is 120-180 min.
7. The preparation method according to claim 5, characterized in that In step S2, in the laser coaxial powder feeding, the laser adopts a circular spot with a diameter of 3-4 mm, a laser scanning speed of 9-11 mm / s, a laser power of 2500-2600 W, and an overlap rate of 40%-50%.
8. The preparation method according to claim 5, characterized in that In step S2, during laser coaxial powder feeding, the powder feeding rate is 16-18 g / min, and the carrier gas flow rate is 1.4-1.5 L / min.
9. The titanium alloy additive manufacturing wear-resistant layer according to any one of claims 1 to 4, or the titanium alloy additive manufacturing wear-resistant layer obtained by the preparation method according to any one of claims 5 to 8, characterized in that: The thickness of the titanium alloy additively manufactured wear-resistant layer is 1-2 mm.
10. The titanium alloy additive manufacturing wear-resistant layer according to claim 9, characterized in that: The wear-resistant layer is WC, Ti2Ni, Ti3Al, (Ti, W) x C 1-x and γ-Ni composite structure.